Study of hemocompatibility and endothelial cell interaction of tecoflex-based electrospun vascular grafts. Issue 1 (11th February 2019) - Chernonosova, Vera S.; Gostev, Alexander A.; Chesalov, Yuriy A.; Karpenko, Andrey A.; Karaskov, Alexander M.; Laktionov, Pavel P.
Abstract: Ensuring long-term functioning and efficient endothelialization of small diameter vascular grafts (VG) is an urgent task of tissue engineering. A solution may be to use electrospun VGs prepared from blends polyurethane with gelatin and/or bivalirudin. Here, properties of 3D matrices were explored by SEM, contact angle measurements and IR spectroscopy, and their interaction with blood and endothelial cells was studied. Introduction of gelatin into matrices enhanced adhesion and proliferation of endotheliocytes and enabled adhesion of platelets, whereas bivalirudin inhibited platelet adhesion while having no negative effect on the adhesion and proliferation of endothelial cells. Graphical Abstract: